1990
DOI: 10.1007/bf02588007
|View full text |Cite
|
Sign up to set email alerts
|

Conservative or surgical treatment of undisplaced (impacted) femoral neck fractures?

Abstract: The treatment of undisplaced femoral neck fractures, having been disputed for the past 50 years, is analysed on the basis of 111 observations during the period of 1981 to 1983. Osteosynthesis proved to be advantageous. Fixation with a three-flanged nail did not increase mortality rate, had no negative effect on late complications, while it could prevent dislocation and permitted full loading at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…1 ) were finally included; these dealt with patients with undisplaced FNFs who were managed either non-operatively or operatively. After careful inspection, we found that >50% of the patients were lost to follow-up in the study of Manninger et al [ 16 ] Additionally, in another study, patients in the surgical group had initially received conservative therapy [ 18 ]. We excluded both studies; 29 studies thus remained.…”
Section: Resultsmentioning
confidence: 99%
“…1 ) were finally included; these dealt with patients with undisplaced FNFs who were managed either non-operatively or operatively. After careful inspection, we found that >50% of the patients were lost to follow-up in the study of Manninger et al [ 16 ] Additionally, in another study, patients in the surgical group had initially received conservative therapy [ 18 ]. We excluded both studies; 29 studies thus remained.…”
Section: Resultsmentioning
confidence: 99%
“…Conservative treatment proponents point out that because most patients would heal without internal fixation when adequately supervised, the risks associated with the operation are not justified in preventing displacement in a tiny fraction of cases (12). Others support using hip arthroplasty to treat elderly patients with non-displaced or impacted NOF fractures to promote early mobility, recovery and lower mortality (13)(14)(15)31). Hemiarthroplasty is thus advised for patients above the age of 75.…”
Section: Groupsmentioning
confidence: 99%
“…The best course of treatment for impacted NOF fractures is still up for debate, and the research in this field is generally lacking. While some surgeons advocate primary surgical stabilisation, others have found positive outcomes with conservative therapy (7)(8)(9)(10)(11)(12)(13)(14)(15). According to reports, the non-operative approach has a success rate of about 85%; however, no published data discusses non-operative treatment indications (10).…”
Section: Introductionmentioning
confidence: 99%